(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of HPV positive oral squamous cell carcinomas by applying p16IHC stain in Pakistani population. Study Design: Descriptive, Cross-sectional study Place and Duration of Study: This study was conducted at the Shaukat Khanum Memorial Hospital and Research Centre for six (06) months from August 2018 to the February 2019. Materials and Methods: In this research 140 patients with oral squamous cell carcinomas, histologically diagnosed, of all ages and either gender. Patients with treatedcases (surgery, chemotherapy, radiotherapy) were excluded. The biopsy was performed and fixed in 10% neutral bufferedformalin. Hematoxylin and eosin were used in the staining of the tissues. The Immunohistochemical (IHC) stainp16 was performed in the same batch according to the specification given by the manufacturer. Results: Mean age in our study was 48:86 ± 9:37 years. Out of the 140 patients, 114(81:43%) were maleand 26(18:57%) were females resulting in male to female ratio of 4:4:1. HPV associated oral squamous cellcarcinomas by p16 immunocytochemistry were found in57(40:71%) patients. It was also found that therewas a significant difference (p <0:05) of HPV associated oral squamous cell carcinomas between differentage groups while no significant difference (p >0:05) of HPV associated oral squamous cell carcinomas werefound between gender and stage of tumor. Conclusion: This study concluded that there is a high frequency of HPV associated oral squamous cellcarcinomas by p16 immunocytochemistry in our population with a positive association with younger age andmale gender.